First report of Neospora caninum from aborted fetuses of cattle, sheep, and goats in Bangladesh. (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: The study aimed to detect Neospora caninum by nested PCR (nPCR) in aborted fetuses of cattle, sheep, and goats in Bangladesh. Materials and Methods: The head portion of each aborted fetus (111) was dissected at each sampling site and transferred to the laboratory in an ice box. Data on risk factors associated with N. caninum infection were simultaneously collected. Deoxyribonucleic acid was extracted from brain tissue to perform nPCR targeting the internal transcribed spacer 1 (ITS1) ribosomal DNA (rDNA) gene of N. caninum and sequencing was performed from the representative positive samples. Results: By nPCR, N. caninum was found in 16.0% of aborted fetuses of cattle, followed by sheep (14.81%) and goats (11.78%). The highest prevalence was found in aborted fetuses of animals during the second trimester (27.78%) of pregnancy aged 2 to 4 years (18.75%). Obtained sequences showed they were completely matched with N. caninum ITS1 rDNA gene deposited in GenBank. Univariate analysis demonstrated that pregnancy stages (trimesters), abortion history of the animals, and access to dogs in animal farms were significantly (p ≤ 0.05) correlated with N. caninum infection. Conclusion: This study represents the first investigation into the molecular detection, phylogenetic characterization, and analysis of risk factors associated with N. caninum in livestock in Bangladesh. According to the research findings, N. caninum infection may have a role in abortion cases and the ensuing financial losses in the nation’s livestock industry. J. Adv. Vet. Anim. Res., 11(3): 618–626, September 2024http://doi.org/10.5455/javar.2024.k811